Titanium Dioxide - Janus, Magdalena (IntechOpen, 2017)
Titanium dioxide is mainly used as a pigment and photocatalyst. It is possible to find it in food, cosmetics, building materials, electric devices, and others. This book contains chapters about characteristics of anatase and rutile crystallographic structure of titanium dioxide and the use of theoretical calculation for photoactivity determination.